A qualitative assessment of mothers' perspectives on hospital and community breastfeeding support in Mississippi. Issue 1 (February 2023) - Gambari, Aishat; Burnham, Laura; Berger, Jacqueline; Annapragada, Bhavana; Bugg, Kimarie; Serano, Andrea; Merewood, Anne
Abstract: The objective of this exploratory qualitative study was to interview breastfeeding mothers who gave birth in three Mississippi areas in 2019, and to record their breastfeeding experiences since the statewide increase in Baby-Friendly activity. Five virtual focus groups were conducted (between February and March 2021) with mothers who gave birth in 2019 and initiated breastfeeding, from the Mississippi Delta, Meridian, and Jackson. Participants discussed their prenatal care, time in the hospital and experience at home after the birth, focusing on breastfeeding education, support, and beliefs. Five key themes regarding participants' hospital and community breastfeeding support experiences and beliefs emerged. Participants reported conflicting breastfeeding support experiences. While several women reported improvements in the breastfeeding environment in Mississippi, some continue to experience inadequate hospital, community, and workplace lactation support. More work needs to be done to ensure optimal prenatal, in-hospital, and at-home breastfeeding education and support in Mississippi.